2009
DOI: 10.1007/s00540-009-0836-2
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of predictors of cerebral vasospasm after ruptured cerebral aneurysm surgery: influence of the location of subarachnoid blood

Abstract: The results indicated that the amount of blood in the right sylvian fissure was significantly associated with the development of angiographic vasospasm after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…First, between total ICH volume and SAH volume, they did not show which one was really associated with development of cerebral vasospasm 5)14). Second, some studies only included patients with Fisher grade 3 4)11). Third, no study of a single modality treated group was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, between total ICH volume and SAH volume, they did not show which one was really associated with development of cerebral vasospasm 5)14). Second, some studies only included patients with Fisher grade 3 4)11). Third, no study of a single modality treated group was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Some quantitative trials have been reported in the literature 1)4)5)11)14). However, those trials had some limitations in the following respects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Heart Association/American Stroke Association guidelines also recommend induced hypertension targeted euvolemia for managing delayed cerebral ischemia (DCI) 4 . The World Federation of Neurological Surgeons (WFNS) grade of the patient at presentation and the location of epicenter of the subarachnoid bleed has shown to be positively correlated with the onset of vasospasm 5, 6 . Since indocyanine green (ICG) flow studies are safe, easily applicable, readily reproducible and now routinely utilized technique during the microvascular clipping of aneurysms, addition of FLOW 800, an automated vascular map study generated by the microscope with the provision for quantitative study of flow velocities and time lag for appearance of the dye between relevant vessels, can help us segregate and outline groups at high-risk of developing post-operative vasospasm and form an evidence-based management algorithm for better therapeutic benefits and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%